2018
DOI: 10.1007/s10532-018-9838-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biotransformation of hexachlorocyclohexane isomers by Dehalococcoides species and an enrichment culture

Abstract: The biotransformation of hexachlorocyclohexane isomers (HCH) by two Dehalococcoides mccartyi strains (195 and BTF08) and an enrichment culture was investigated and compared to conversion by the obligate anaerobic strain Clostridium pasteurianum strain DSMZ 525. The D. mccartyi strains preferentially transformed γ-HCH over α-HCH and δ-HCH isomers while β-HCH biotransformation was not significant. In case of the enrichment culture, γ-HCH was preferentially transformed over the δ-HCH, β-HCH and α-HCH isomers. Maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Several studies reported that the microbial anaerobic degradation of lindane is different from aerobic degradation (Endo et al, 2005;Bashir et al, 2018). Dichloro-elimination and dehydrochlorination appear to be the main processes during the transformation of lindane via tetrachlorocyclohexene (TCCH) into lower chlorinated products under the anoxic conditions of aquifer sediments (Lal et al, 2010).…”
Section: Anaerobic Degradationmentioning
confidence: 99%
“…Several studies reported that the microbial anaerobic degradation of lindane is different from aerobic degradation (Endo et al, 2005;Bashir et al, 2018). Dichloro-elimination and dehydrochlorination appear to be the main processes during the transformation of lindane via tetrachlorocyclohexene (TCCH) into lower chlorinated products under the anoxic conditions of aquifer sediments (Lal et al, 2010).…”
Section: Anaerobic Degradationmentioning
confidence: 99%
“…and Sphingobium sp. in batch experiments 32,33 and landscape level in the groundwater in Bitterfeld. 34 Recently, CSIA was successfully applied to characterize the transformation of HCHs in garden soil− plant and hydroponic systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Of the currently-characterized OHRB, Dehalococcoides represents a unique lineage for reductive dechlorination of a wide range of organohalides, and is an optimal candidate for applying the Bio-RD-PAO process. For example, Dehalococcoides is one of the only two organohaliderespiring genera able to dechlorinate hexachlorocyclohexane (HCH) (Doesburg et al, 2005;Maphosa et al, 2012;Bashir et al, 2018). Dehalococcoides transforms (α, β, γ, δ)-HCH to monochlorobenzene and benzene (Bashir et al, 2018), which enables their efficient and complete degradation via subsequent PAO.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For example, Dehalococcoides is one of the only two organohaliderespiring genera able to dechlorinate hexachlorocyclohexane (HCH) (Doesburg et al, 2005;Maphosa et al, 2012;Bashir et al, 2018). Dehalococcoides transforms (α, β, γ, δ)-HCH to monochlorobenzene and benzene (Bashir et al, 2018), which enables their efficient and complete degradation via subsequent PAO. For reductive dichlorination of PCBs, Dehalococcoides, Dehalogenimonas and Dehalobacter can remove flanked meta-/para-chlorines from PCBs with different specificities and generate a variety of lowly-chlorinated PCBs for subsequent degradation using PAO.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%